2021
DOI: 10.1016/j.crstbi.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

3D interaction homology: Hydropathic interaction environments of serine and cysteine are strikingly different and their roles adapt in membrane proteins

Abstract: Atomic-resolution protein structural models are prerequisites for many downstream activities like structure-function studies or structure-based drug discovery. Unfortunately, this data is often unavailable for some of the most interesting and therapeutically important proteins. Thus, computational tools for building native-like structural models from less-than-ideal experimental data are needed. To this end, interaction homology exploits the character, strength and loci of the sets of interactions that define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 89 publications
2
25
0
Order By: Relevance
“…Additionally, all residues, apart from glycine and proline, exhibit their highest solvent accessibility in the left-hand α-helix region. These observations were anticipated, as we have seen them previously ( Ahmed et al, 2015 , Ahmed et al, 2019 , AL Mughram et al, 2021 , Catalano et al, 2021 ), and they are consistent with literature observations of SASA with respect to secondary structure ( Lins et al 2003 ).
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, all residues, apart from glycine and proline, exhibit their highest solvent accessibility in the left-hand α-helix region. These observations were anticipated, as we have seen them previously ( Ahmed et al, 2015 , Ahmed et al, 2019 , AL Mughram et al, 2021 , Catalano et al, 2021 ), and they are consistent with literature observations of SASA with respect to secondary structure ( Lins et al 2003 ).
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…We believe that the relative solvent accessibility and the hydropathic natures of residues found in both types of proteins are secondary structure-dependent and shed light on an important relationship between structure and protein folding in polar and hydrophobic environments. This work supplements findings of our previous contributions studying the hydropathic environments of specific amino acid types ( Ahmed et al, 2015 , Ahmed et al, 2019 , AL Mughram et al, 2021 , Catalano et al, 2021 , Herrington and Kellogg, 2021 ), by encompassing all residue types in the context of soluble and membrane protein environments. As a result, we highlight notable differences in residue populations, SASAs and interaction characters between both.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Recently, in our report on phenylalanine, tryptophan, and tyrosine, we showed that the subtle effects of π-π and π-cation interactions are encoded in their 3D hydropathic interaction maps (AL Mughram et al, 2021). In a report on serine and cysteine we highlight the major structural features-similarities and differences-between these two isosteric residues (Catalano et al, 2021). Importantly, our analyses describe residues by cataloguing their environments in terms of interactions and not identity.…”
Section: Three-dimensional Interaction Homologymentioning
confidence: 91%